Social Networks as Predictors of Colorectal Cancer Screening in African Americans - Ernest Alema-Mensah; Selina Smith; Mechelle Claridy; Victor Ede; Benjamin Ansa; Daniel Blumenthal (Georgia Southern University, 2017)
Background: Early detection can reduce colorectal cancer (CRC) mortality by 15%-33%, and screening is widely recommended for average-risk adults beginning at age 50 years. Colorectal cancer mortality rates are higher in African Americans than in whites, while screening rates are somewhat lower. Individual social networks can reduce emotional and/or logistical barriers to healthpromoting but distasteful procedures such as CRC screening. The aim of this study was to examine social network interactions, and their impact on CRC screening among African Americans. We hypothesized a positive association between social network index (SNI) scores and CRC screening. Methods: In a community intervention trial with four arms, we previously demonstrated the efficacy of a small group educational intervention to promote CRC screening among African Americans. This intervention outperformed a one-on-one educational intervention, a reduced out-of-pocket expense intervention, and a control condition. In the present analysis, we compared the SNI scores for participants in the small group intervention cohort with a comparison group comprised of the other three cohorts. Social networks were assessed using the Social Network Index developed by Cohen. Results: Small group participants had a significantly higher network diversity score (Mean difference 0.71; 95% CI, 0.12-1.31; p=0.0017) than the comparison group. In the second component of the SNI score - -the number of people talked to over a two week period -- the small group intervention cohort also scored significantly higher than the comparison group. (Mean difference, 9.29; 95% CI, 3.963-14.6266; p=0.0004). Conclusions: The findings suggest that social interaction and support was at least partially responsible for the relatively high post-intervention screening rate in the small group intervention participants. Education in small groups could foster strong social networks. Strong and positive network diversity and a large number of people in social networks may enhance CRC screening rates among African Americans.